PENGENDALIAN LAHAN PERTANIAN PANGAN BERKELANJUTAN OLEH DINAS PERTANIAN KABUPATEN SIAK (STUDI KASUS DI KECAMATAN BUNGARAYA) - Elen, Ratu; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Control as an action taken before the process, during the process and after the process, until the final results are known. Protection of sustainable food agricultural land is a system and process in planning and establishing, developing, utilizing and fostering, controlling, and monitoring food crops and their area continuously. The occurrence of the conversion of plantation land into agricultural land and the absence of a target in the conversion of functions has become a phenomenon in Control of Sustainable Agricultural Food Lands By The Department Agriculture (Case Study in Bungaraya Subdistrict). The purpose of this study was to find out how the Control and obstacle factor of Sustainable Agricultural Food Lands in Bungaraya Subdistrict. The theoretical concept used by Malayu S.P. Hasibuan (2017: 245) which consists of four control processes namely determining standards that will be used as the basis of control, measuring implementation or results that have been achieved, comparing implementation or results with standards and determining irregularities if any, and taking corrective actions if there are deviations so that the implementation and objectives are in accordance with the plan. The research method is a type of qualitative research, the selection of informants using purposive techniques and snowball sampling. Data collection techniques are through observation, interviews and documentation. The result showed that the Control of Sustainable Agricultural Food Lands By The Department Agriculture (Case Study in Bungaraya Subdistrict) has not been implemented optimally. As for the inhibiting factors include Human Resources managers, public awareness is still lacking and facilities and infrastructure. Â Keywords: Control, Function Transfer, Sustainable Food Agriculture Land